2007
DOI: 10.1038/sj.bjp.0707193
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activity of a hydrogen sulphide‐releasing derivative of mesalamine (ATB‐429) in a mouse model of colitis

Abstract: Background and Purpose: Mesalamine is the first-line therapy for colitis, but it lacks potency and is only effective for mild-tomoderate forms of this disease. Hydrogen sulphide has been shown to be a potent, endogenous anti-inflammatory substance, modulating leukocyte-endothelial adhesion and leukocyte migration. The purpose of this study was to determine if an H 2 Sreleasing derivative of mesalamine (ATB-429) would exhibit increased potency and effectiveness in a mouse model of colitis. Experimental Approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
165
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(176 citation statements)
references
References 33 publications
8
165
0
1
Order By: Relevance
“…Nonetheless, as a therapeutic tool, pharmaceutical-grade Na 2 S shows great potential and has been successfully used to prevent and treat myocardial infarction, ischemia-reperfusion injury and endotoxic shock [112,113]. It is Table 2 By sharp contrast, no effect was observed with mesalamine or ADT-OH treatment alone, suggesting protective effects in addition to H 2 S release [111] Male Wistar rats: Carageenan-induced hindpaw edema The study concluded that the additional anti-inflammatory effect of S-diclofenac was due to H 2 S release [134] Male Wistar rats: Trinitrobenzene sulfonic acid-induced colitis [125] Male Swiss albino mice: Cecal ligation and puncture-induced sepsis PPT-A gene expression and substance P levels whereas NaSH increased substance P levels and lung injury [71] Balb/C mice: Acute pancreatitis and associated lung inflammation induced by cerulein…”
Section: H 2 S Donor Molecules and Inflammation: Notes Of Cautionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nonetheless, as a therapeutic tool, pharmaceutical-grade Na 2 S shows great potential and has been successfully used to prevent and treat myocardial infarction, ischemia-reperfusion injury and endotoxic shock [112,113]. It is Table 2 By sharp contrast, no effect was observed with mesalamine or ADT-OH treatment alone, suggesting protective effects in addition to H 2 S release [111] Male Wistar rats: Carageenan-induced hindpaw edema The study concluded that the additional anti-inflammatory effect of S-diclofenac was due to H 2 S release [134] Male Wistar rats: Trinitrobenzene sulfonic acid-induced colitis [125] Male Swiss albino mice: Cecal ligation and puncture-induced sepsis PPT-A gene expression and substance P levels whereas NaSH increased substance P levels and lung injury [71] Balb/C mice: Acute pancreatitis and associated lung inflammation induced by cerulein…”
Section: H 2 S Donor Molecules and Inflammation: Notes Of Cautionmentioning
confidence: 80%
“…It is highly unlikely that cells or tissues are ever exposed to H 2 S generated in such a rapid manner, generating high local concentrations of H 2 S, since endogenously produced H 2 S through CSE and CBS is relatively slow and sustained [68,92,109,110]. Furthermore, injection of these salts into animals results in a minimal increase in plasma H 2 S concentrations over a very short period of time [21,33,68,111]. Commercially available NaSH rarely exceeds 70% purity and it is possible that the disparate physiological findings with NaSH could reflect the varying amounts of chemical impurities present in the NaSH.…”
Section: H 2 S Donor Molecules and Inflammation: Notes Of Cautionmentioning
confidence: 99%
“…The redox potential of H 2 S in the vascular tissue may also be related to the recent finding that H 2 S mediates vasoactivity in an oxygen-dependent manner (29). Moreover, inhibition of endogenous H 2 S synthesis reduces leukocyte rolling velocity and increases leukocyte adherence to mesenteric postcapillary venules under baseline conditions, whereas NaHS treatment prevents leukocyte-endothelial cell adhesive interactions following exposure to TNF-␣ (13,15). The former results indicate that basal H 2 S production serves as an endogenous modulator of leukocyte-endothelial cell adhesive interactions, whereas the latter observation indicates that H 2 S donors may be effective in preventing adhesive responses induced by proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…A diclofenac derivative has been shown to reduce LPS-induced iniltration of neutrophils into the lung and liver [41]; also an H 2 S-releasing derivative of mesalamine profoundly reduced granulocyte iniltration in a mouse model of colitis [42] with efect signiicantly greater than that observed in the parent molecules in each case. H 2 S-releasing diclofenac was also realized to be more potent than diclofenac in reducing paw edema in the carrageenan-induced paw edema model in rat.…”
Section: H 2 S-releasing Derivatives Of Anti-inlammatory Drugsmentioning
confidence: 99%